Moroccan Arabic borrowed circumfix from Berber - Zellou, Georgia (Linguistica (Ljubljana), 2011)
Moroccan Arabic (MA) has a derivational noun circumfix /ta-...-t/ that is borrowed from the neighboring Berber languages. This circumfix is highly productive on native MA noun stems but not productive on borrowed Berber stems (which are rare in MA). This pattern of productivity is taken to be evidence in support of direct borrowing of morphology (c.f. Steinkruger and Seifart 2009) and against a theory where borrowed morphology enters a language as part of unanalyzed complex forms which later spread to native stems (c.f. Thomason and Kaufman 1988; Thomason 2001); furthermore, it challenges the principle of a "borrowability hierarchy" (c.f. Haugen 1950) where lexical morphemes are borrowed before grammatical morphemes. Additionally, the prefixal portion of the MA circumfix, ta-, is a complex (presumably unanalyzed) form from the Berber /t-/ feminine + /a-/ absolute state. Moreover, the morpheme in MA has been borrowed as a derivational morpheme while the primary functions of the donor morphemes in Berber are inflectional. This case of a borrowed circumfix is examined as an instance which does not conform to traditional typologies of language change through contact patterns and how the boundaries between morphological categories (i.e. inflectional/derivational) are transformed in a language contact situation.
Keywords: arabe marocain; arabščina; berberski govori; besedotvorje; formation des mots; jeziki v stiku; langues en contact; maroška arabščina; morphologie; oblikoslovje; word formation